Criminal Code of the Republic of Belarus: results, problems and prospects - Savenok, Anatoly L. (Journal of the Belarusian State University. Law, 2019)
The issues of criminal lawmaking and the application of the Criminal Code of the Republic of Belarus are considered. It is noted that the domestic criminal law has solved the task of transition from a planned economy to a market one that stood before it. It is proposed to develop and adopt in the prescribed manner separate rules for the preparation of a draft criminal law. This measure will significantly improve the quality of criminal law and ensure their effectiveness.
Keywords: legislative technique; content of criminal law; legal monitoring; interpretation of norms; effectiveness of criminal law; quality of criminal law; competition of norms